2009
DOI: 10.1177/1753193409347686
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal intercarpal ligament capsulodesis for predynamic and dynamic scapholunate instability

Abstract: We treated a prospective series of 18 patients (nine men and nine women) with a mean age of 35 years (range 15 to 57), with chronic predynamic or dynamic scapholunate instability by a dorsal intercarpal ligament capsulodesis using the modified Mayo technique. All the patients were assessed by the modified Mayo wrist score and DASH questionnaire. Wrist arthroscopy was done in all patients before open surgery in order to grade the scapholunate instability and correlate the findings with the radiographic and MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
1
25
0
6
Order By: Relevance
“…La ligamentoplastie scapholunaire au ligament scaphotriquétral a été décrite par Berger et al en 1995 [1]. Peu d'études cliniques ont permis d'étudier les résultats de cette technique chirurgicale [11,12].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La ligamentoplastie scapholunaire au ligament scaphotriquétral a été décrite par Berger et al en 1995 [1]. Peu d'études cliniques ont permis d'étudier les résultats de cette technique chirurgicale [11,12].…”
Section: Discussionunclassified
“…Luchetti et al, en 2009, ont publié une série comparable à la nôtre avec un recul plus important de 48 mois mais sur seulement 18 patients [11]. Ils constatent un arc de mobilité du poignet de 1238 contre 1188 dans notre série.…”
Section: Discussionunclassified
“…Luchetti et al 14 presented 18 patients treated with dorsal intercarpal ligament capsulodesis for predynamic and dynamic instability, and found that pain decreased and grip strength increased. Misra and Hales 15 reported similar success with Blatt's capsulodesis for predynamic and dynamic instability, as measured by grip strength and pain.…”
Section: The Evidencementioning
confidence: 98%
“…Originally described as detachment of the radial-sided fibers of the DIC from the scaphoid, trapezium, and trapezoid, the distal half of the DIC can be detached following a ligament-sparing approach to the wrist. 27,28 After ensuring reduction of the scaphoid and lunate, a trough is created on the dorsal aspect of the scaphoid, distal to its axis of rotation, to act as a dorsal force opposing flexion of the distal pole. A suture anchor is placed within the bony trough and the radial side of the transected DIC can be tied down, into the trough, to augment the direct ligamentous repair.…”
Section: Operative Technique (Direct Repair With Dorsal Intercarpal Lmentioning
confidence: 99%